Pengaruh Leverage Dan Likuiditas Terhadap Financial Distress Dengan Pemoderasi Profitabilitas - Nur Ainiyah; M Bahril Ilmiddaviq (Economics and Digital Business Review, 2025)
Companies in the technology sector cannot be separated from this. Technology companies face complex dynamics, including short product life cycles, high investment requirements, and intense competition. Therefore, innovation is significant for a company's survival amidst competitive competition. Companies that constantly innovate their products can better survive competitive pressures and improve their market position. Technology companies often have to allocate large budgets for research and development, which can increase Leverage and reduce liquidity. The company could face significant financial stress if these investments do not generate sufficient income. This research aims to analyze the effect of Leverage and liquidity on Financial Distress with profitability as a moderating variable. The research results show that Leverage and liquidity partially influence Financial Distress, and profitability can strengthen the influence of each independent variable (Leverage and liquidity) on Financial Distress. Profitability is a moderating variable, which is a quasi-moderator variable. In the case of the profitability variable as a Quasi Moderator, profitability can be used as an independent variable that can stand alone and influence Financial Distress.